Casuarina cunninghamiana Miq. (River sheoak) in Florida and its Potential as a Windbreak Plant for Citrus Groves - William S. Castle (EDIS, 2008)
HS-1139, a 12-page illustrated fact sheet by William S. Castle, compiles pertinent information and provide an historical perspective for environmentalists, biologists, scientists and other interested parties regarding the Casuarina species in Florida which are presently classified as invasive and illegal to possess or propagate. Includes references and a summary of regulatory authorities. Published by the UF Department of Horticultural Sciences, May 2008.